Pengaruh Variasi Sudut Kampuh V Terhadap Kekuatan Sambungan Stainless Steel 316 pada Pengelasan Tungsten Inert Gas - Eduar, Dionisius; Rosehan, Rosehan; Lubis , Sobron Yamin (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine the effect of variations in the V seam angle with TIG welding on the strength of the welding joints in each 316 stainless steel specimen and to find out how much the strength value of the welding joints is in stainless steel 316 after a tensile test is carried out. Types of research methods and data collection will start from 316 stainless steel plate welding with TIG welding. Welding will be carried out with a variation of the V seam angle of 30o, 45o, and 60o at each 120 A welding current and 15L/min argon discharge. After welding, the stainless steel will be cut according to ASTM E8 standard sizes and followed by a tensile test to determine the effect of variations in seam angles on the strength of the welded joints. Based on the results of the test data obtained, it shows that (1) the tensile stress value is directly proportional to the strain. The greater the tensile stress value, the greater the strain value will be. (2) The results of the tensile test show that the greater the seam angle, the higher the resulting tensile stress. The highest tensile strength was the specimen with a seam angle of 60o which was 511.4 Mpa, while the lowest tensile strength was the specimen with a seam angle of 30o which was 378.2 Mpa. (3) The results of the tensile test show that the greater the seam angle V, the greater the tensile stress so that the strain is also greater. The highest strain for specimens with a seam angle of V 60o is 7.9, while the lowest strain is for specimens with a seam angle of V 30o which is 2.9. (4) The results of the calculation of tensile stress and strain obtained the highest modulus of elasticity for the V 60o seam corner specimen, namely 15358.358, while the lowest value was for the V 30o seam corner specimen, namely 12629.189.